PM.44 Pregnancy Outcomes in Black Women with Chronic Hypertension in the UK. (26th April 2013) - Homsy, M; Bramham, K; Parnell, B; Nelson-Piercy, C; Chappell, LC
Abstract : Introduction: Women with chronic hypertension (CHT) have poor pregnancy outcomes. Black ethnicity is associated with both adverse pregnancy events, and CHT. Data regarding pregnancy outcome for black women in the UK are limited. Aims: 1) To assess pregnancy outcomes in women with CHT according to ethnicity; 2) To evaluate changes in pregnancy outcome over a decade Methods: Women with CHT who delivered at St. Thomas' Hospital between 2001–2011 were identified from a hospital database, and pregnancy outcomes extracted. Outcomes between black and white women were compared. Multiple pregnancies were excluded. Results: Black women had significantly worse neonatal outcomes than white women with CHT (Table ). There were no significant differences in CHT pregnancy outcome between 2001–2011. Conclusion: Black ethnicity is associated with significantly worse pregnancy outcomes in women with CHT. There have been no improvements in outcome over the last decade for women with CHT managed in our unit. Underlying mechanisms for adverse events in women with CHT should be studied and racial differences explored.